Why not lie? Costs enforce honesty in an experimental signalling game - Polnaszek, Timothy J. (The Royal Society, 2014)
Communication depends on reliability. Yet, the existence of stable honest signalling presents an evolutionary puzzle. Why should animals signal honestly in the face of a conflict of interest? While students of animal signalling have offered several theoretical answers to this puzzle, the most widely studied model, commonly called the ‘handicap principle’, postulates that the costs of signals stabilize honesty. This model is the motivating force behind an enormous research enterprise that explores signal costs—whether they are physiological, immunological, neural, developmental or caloric. While there can be no question that many signals are costly, we lack definitive experimental evidence demonstrating that costs stabilize honesty. This study presents a laboratory signalling game using blue jays (Cyanocitta cristata) that provides, to our knowledge, the first experimental evidence showing honesty persists when costs are high and disappears when costs are low.